A single stage ZVS Power factor correction converter - Ravivarman, G; Poorani, S (International Journal of Engineering and Technology, 2018)
The aspects with respect to control strategies power factor correction (PFC) converter are examined. Research effort in focus to minimized switching stress for improving better efficiency in power rating is 500W/48V, is achieved by using soft switching. In this suggested converter and switching scheme ZVS voltage stress is shaped. Added to this power loss is minimized. A 500W/48V prototype is proposed to serve the concept proof, which exhibits 92.69% peak efficiency at low input line voltage.Â Â